The Form of Erythrocytes and Laser Doppler Flowmetry of Skin with ACNE and Use of Medication FarGALS in its Comprehensive Treatment - Khashimov F.F.1, Baibekov I.M.1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Using the express method of a thick smear and morphometry, the state of erythrocytes obtained from theacne and finger region has been studied. Using laser Doppler flowmetry, the state of microcirculation of theskin of the finger and the acne location area has been studied.It has been found out that comprehensive treatment with the use of FarGALS promotes the reduction inblood of pathological forms of erythrocytes and the restoration of microcirculation parameters.